Analysis of entropy generation in magnetohydrodynamic convective flow of nanofluids within a wavy trapezoidal enclosure: A Brinkmann-Forchheimer model using finite element method - Asad Ali; Muhammad Ayaz; Zahoor Ahmad; Ashraf M. Marei (Case Studies in Thermal Engineering, 2025)
This study presents a computational investigation of entropy generation in MHD free convection of Cu-water nanofluid within a wavy trapezoidal cavity. The chamber contains a warmed obstacles positioned at the center. The cavity's left and right walls are actively cooled to a temperature of Tc, while an insulated boundary is utilized to the wavy top wall. The inner circular rings and the bottom wall are warmed to a stable temperature of Th. The Darcy-Forchheimer model is used to analyze the permeable domain. The governing equations were addressed using the GFEM within the COMSOL Multiphysics software framework. The study examines the impact of various physical parameters on thermal performance and fluid flow, such as porosity (ℇ), volume fraction (ϕ), cylinder radius (R), (Ra) and (Ha). The outcomes indicate that the nanofluid's behavior is significantly influenced by the existence of a magnetic field, and increasing the Rayleigh and Hartmann numbers improves the cavity's thermal efficiency. The temperature profile within the system is minimally affected by the radius of the inner circular ring. Additionally, the Nuavg rises as the Rayleigh number and porosity increase but declines with an augmentation in the Hartmann number. Furthermore, with the increasing (Ra),(ϕ) and, the STotal increased by 94.2%and8.4% respectively. Conversely, STotal decreased by 36.8% with the increase in Ha. These outcomes improve thermal regulation and energy efficiency, optimizing performance in solar collectors, solar dryers, and heat exchangers by enhancing heat transfer and reducing thermal losses.